Digital filters creation of seabed image processing - Ramašauskas, Olegas; Rupšienė, Ilona; Kazlauskas, Mantas (Lietuvos matematikos rinkinys, 2015)
Nowadays visual information is extracted using a variety of physical methods and cannot always be easily perceived by the human eye, properly recognized and classified. Such large amounts of information provided by the modern image-making equipment is difficult and sometimes impossible objectively evaluate. Research of digital images carried out at the Klaipėda University with a focus on marine research topic. The combination of new underwater technology as remotely operating vehicles, high-resolution video imagery, and seafloor mosaics creating provides new opportunities for marine geological or biological studies. While these underwater techniques are now well-engineered, there is still a lack of methods for the automatic analysis of the acquired image data. In this paper, the video mosaic quality and processing problems discussed. Believes that the versatility of abstract techniques to tailor the fields of biomedical sciences, applied robotics and elsewhere. This could be listed as a main purpose of presented work.